PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA ARAB BERBASIS ANDROID UNTUK MAHᾹRAT AL ISTIMᾹ’ KELAS 8 SMP - Hijriyah, Umi; Basyar, Syarifudin; Koderi, Koderi; Erlina, Erlina; Aridan, Muhammad; Hidayatullah, Muhammad Subkhi (STIQ Amuntai, 2022)
Arabic as a foreign language in its learning often encounters problems. For example, in the aspect of listening skills. To solve these problems, concrete efforts are needed through the development of learning tools or media that can support this difficult Arabic language learning process. This research belongs to the type of Research and Development (R&D) with the ADDIE model with 5 stages, namely the process to analyze, design products, develop products, test processes, and development evaluation processes. The result of the research is the presence of a learning media product for android-based Arabic language in learning listening skills that can be operated on smartphones for students in grade VIII SMP / MTs. This product has a qualified level of feasibility to be used in learning activities with the results of the feasibility test of 2 types of validation. Namely validation with material expert validators and media expert validators by obtaining an average percentage value of 95% by material experts 95.55% by media experts or in